Soft tissue myxoma: report of an unusual case located on the gingiva - Vittoria Perrotti (Blackwell Synergy, 2006)
Background: Soft tissue myxoma of the oral cavity is rare. Only three cases of myxoma of gingiva have been reported in the literature. We present a case of soft tissue myxoma arising from the left maxillary adherent gingiva in a 42-year-old female patient. Methods: Histological examination showed spindle-shaped cells in a myxoid stroma. Immunohistochemical stains with S-100 protein were negative, while those with vimentin were positive. Results: Clinical examination revealed a soft tissue mass, with tense elastic consistency on palpation. The overlying mucosa was normal and healthy. A clinical diagnosis of fibroma was given. Histological examination showed spindle-shaped and stellate cells, arranged in a myxoid fibrous stroma, with collagen fibres distributed uniformly. Scattered islands or strands of inactive odontogenic epithelium were present. On the basis of the histological and immunohistochemical findings, the final diagnosis was soft tissue myxoma. Conclusions: Further studies are necessary to clarify the origin and histogenesis of this lesion.